EARLY PRODUCE OF ETHIOP VARIETY OF TABLE BEET - Stefaniuk С.; Hel І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article presents the results of field studies on the influence of sowing dates (early spring and late autumn) and types of cover (agrofibre, polyethylene film, no covering) on the formation of yield and biochemical composition of bunch products of Ethiop table beet in the Western Forest-Steppe zone of Ukraine. The experiments were conducted in 2023–2024 on the fields of Lviv National University of Horticulture. The results of the research showed that the highest yield of bunch products (74.1 thousand bunches/ha) was obtained under conditions of early spring sowing with polyethylene film covering. When agrofibre was used, the yield decreased by 3.6 thousand bunches/ha, and when grown without covering, by 6.8 thousand bunches/ha. Winter sowing under all types of covering was accompanied by a decrease in yield, which is explained by unfavourable weather conditions. Biochemical analysis of the products showed that the highest content of dry matter, sugars, and vitamin C was observed in the variants with the use of coverings, especially polyethylene film. The lowest nitrate content was recorded in the leaves of plants during early spring sowing under agrofibre. The results obtained confirm the feasibility of using polyethylene film to cover crops of the Ethiop variety of table beet in early spring, which ensures both an increase in yield and an improvement in the biochemical indicators of the product. Considering the environmental and economic aspects, the use of agrotextile is also promising, especially in small and medium-sized farms. The studies confirm the need for further improvement of the technology for growing bunch beetroot, taking into account climate change, variety characteristics, and agrotechnical measures.